Generación de energía eléctrica a través de biogas para la avícola de la hacienda La Victoria. - Guanochanga Amores, William Alexander (2020)
The Victoria estate, which is located in the province of Pichincha, canton Mejia, La Calera sector, has a considerable number of head of cattle that generate a 62 000 Kg of fresh manure per day, 20% of these excreta are used in the elaboration of fertilizer by vermiculture, that is why in this document four case studies were carried out with 25%, 50%, 75%, 80% of the total excrement of cattle and thus being able to determine what is the amount of biogas that occurs in each of the cases with the purpose or the need to supply electricity to the poultry farm in the peak demand period which is the period where electric power costs more than in the demand period base and in the period of average demand, reducing energy costs. Therefore, in order to reduce the problem or the need described above, this work has the fundamental objective of sizing a system of electricity generation using biogas that can be obtained from excrements of cattle from the Victoria estate. To fulfill this objective, four case studies were carried out with different percentages of the total amount of cattle excrement with all its corresponding stages and thus to determine the amount of biogas and from this the motor-generator is sized based on biogas, from which we will obtain the necessary power to supply the maximum demand for poultry, as well as a technical-economic analysis to determine its feasibility by developing the calculation of NPV and IRR. And finally it should be noted that the biol generated was used as fertilizer for bluegrass and white and red clover crops, which are used as food for livestock.